TOURISTS AND OPPORTUNITIES TO FILL HOTEL OCCUPANCY. (CASE STUDY AT NUSA DUA BEACH HOTEL) - Agus Deni Permadi; I Wayan Kiki Sanjaya; Nararya Narrotama (Institut Pariwisata dan Bisnis Internasional, 2016)
Chinese tourists visit that increase each year have led to numerous impacts on the tourism industries, such as increasing the opportunities to invest in building more accommodation facilities to accommodate the influx. In addition to the development, there are also negative effects caused by it, such as intense competition among service providers to meet the level of occupancy. NDBH as one of the best hotels in Bali is quite keen to see these opportunities, by making advantage of the Chinese tourists visit in Bali. The research was conducted to study their potential room occupancy in NDBH to the viewpoint of academic realm. 2) Perform arguments proofing on negative issue of the scholars’ thinking paradigm on our current tourism concerning the Chinese tourists. By using SWOT analysis it is found out that: 1) The strength of Chinese tourists rely on its huge population, a positive contributions against occupancies, and diverse classification of Chinese tourists, 2) The weaknesses of the Chinese tourists are; they are having lack of Behavior, They speaking influent English, and they tend to make reservation in a short notice, 3) Opportunities of Chinese tourists are; travel agents are distributing many Chinese tourists in Bali making them accessible, and group of Chinese tourists help boost occupancy rates, 4) The threat of Chinese tourists are; it is likely to harm the Cross Culture of the hotel, Chinese travelers are not a loyal customer (Price Oriented), operational processes has hampered hotels, and hotel loss profit on sub-department. Hopefully this research can help interested parties, especially those who deal directly with tourists from China, in order to take appropriate measures and policies in the future.